1999
DOI: 10.1111/j.1349-7006.1999.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Role of T and Tn Tumor‐associated Antigens in Adhesion between a Human Breast Carcinoma Cell Line and a Normal Human Breast Epithelial Cell Line

Abstract: The possibility that tumor-associated antigens T and Tn act as adhesion molecules between normal and malignant breast epithelial cells at the early stages of recognition in the metastatic pathway was examined in vitro. The adhesive specificity of the antigens was assessed by means of in vitro adhesion tests between a carcinomatous breast cancer cell line (ZR75-30) and a normal epithelial breast cell line (HLB100) using both monoclonal antibodies and lectins specific as well as nonspecific for each antigen. Adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…The potential number of people that could possibly be helped with a vaccine to a target on all of these cancers is staggering. TF-Ag is also a promising target because adhesion mediated by TF-Ag plays a role in metastasis [135,141,142,153,156,157]. This role in metastasis is important because a humoral immune response generated by a vaccine to TF-Ag could kill the tumor cells by ADCC and CDC and in addition could block the ability of the tumor cells to spread.…”
Section: The Mucin Related Tumor-associated Antigensmentioning
confidence: 99%
“…The potential number of people that could possibly be helped with a vaccine to a target on all of these cancers is staggering. TF-Ag is also a promising target because adhesion mediated by TF-Ag plays a role in metastasis [135,141,142,153,156,157]. This role in metastasis is important because a humoral immune response generated by a vaccine to TF-Ag could kill the tumor cells by ADCC and CDC and in addition could block the ability of the tumor cells to spread.…”
Section: The Mucin Related Tumor-associated Antigensmentioning
confidence: 99%
“…Its widespread presence has been noted on tumors of epithelial origin but it is absent on tumors of ectodermal and mesodermal origin (8). Studies using monoclonal antibodies and lectins have demonstrated the expression of sialylated and nonsialylated forms of Tn antigen in gastrointestinal tumors, particularly in colon cancer (9,10), pancreatic (11) and gastric (12) cancers, in ovarian (13) and uterine (14) cancers, and in numerous cases of breast cancer (14)(15)(16)(17)(18). Tn antigen mostly occurs in malignant breast lesions, invasive carcinomas and their metastases, but it has also been found in benign lesions.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, we tested several other cell lines, including a nontumorigenic transformed breast epithelial cell line (HBL100) 39 and the aggressively metastatic MDA-MB-231 40 breast cancer cell line. We also tested the poorly metastatic melanoma cell line A375P and its metastatic variant melanoma cell line A375SM, 41 and three osteosarcoma cell lines (MG63, SOAS-2, and TA29), a lymphoblastic leukemia (Z119), and four acute mylogenous leukemia cell lines (AML-2, AML-3, KBM5, and KBM7).…”
Section: Synergy Is Cell-type Specificmentioning
confidence: 99%